Towards a future battlefield forensics framework: a NATO action research case study - Rietveld, Rikke Michelle (Scandinavian Military Studies, 2025)
This article examines the key challenges and requirements for achieving interoperability in NATO battlefield forensics – the application of scientific methods to collect, analyse, and disseminate information, intelligence and evidence in conflict zones, bridging military and civilian domains. The article presents findings from three empirical inputs: a scoping mission and doctrinal review, NATO exercises and experimentation, and stakeholder engagement through surveys, workshops, and conferences. Five cross-cutting themes were identified: conceptual ambiguity; capability shortfalls; fragmented legal frameworks; weak interagency cooperation; and shared future needs. The analysis demonstrates that interoperability in NATO battlefield forensics is constrained not only by technical gaps but also by doctrinal, legal, organisational and cultural barriers. The article concludes that progress depends on three priorities: institutionalising a staffed Technical Exploitation (TE) function and fit-for-purpose doctrine; harmonising legal frameworks for operational and judicial use; and building predicable civil-military pathways and competence. It also highlights the need to overcome cultural barriers, notably the legacy perception of TE as a narrow counter-IED tool and the tendency to exercise blindness: the assumption that exploitation processes will function automatically in crises.
The data that support the finding of this study are available on request from the corresponding author (RMR). Some data are not publicly available due to restrictions – for example, where they contain information that could compromise the privacy of research participants and/or consist of NATO or national classified documents.
Keywords: battlefield forensics; military intelligence; interoperability; technical exploitation; action research; military culture